Analisis Pemanfaatan Program Posbindu dalam Deteksi Dini dan Pencegahan Penyakit Tidak Menular di Puskesmas Palibelo - Mujiburrahman Mujiburrahman (Pusat riset dan Inovasi Nasional, 2025)
Non-Communicable Diseases (NCDs) are the leading cause of death globally. The Posbindu PTM program serves as an initiative for early detection and prevention of NCDs through community empowerment. This study aims to analyze the factors influencing the utilization of the Posbindu PTM program in the working area of Palibelo Health Center, Bima Regency. This quantitative research used a cross-sectional approach, involving 100 purposively selected respondents. Data were analyzed using the chi-square test. The results showed that education level and knowledge significantly affected the utilization of Posbindu services (p < 0.05). Respondents with higher education and better knowledge were more likely to use Posbindu services actively. However, lack of information and inadequate socialization were identified as major barriers to optimal utilization. Strengthening public health education and promotion is essential to enhance community participation in the Posbindu PTM program.